Implementasi Produk Pembiayaan Kredit Usaha Rakyat (KUR) Mikro Pada PT. Bank Syariah Indonesia Kantor Cabang Pembantu Binjai Sudirman - Nurhaliza Nurhaliza; Ahmad Sanusi Lukman; Sri Wahyuni Hasibuan (AGHNIYA : Jurnal Ekonomi Islam, 2022)
The research aims to find out the criteria for customers who receive Sharia Micro KUR financing products at PT. BSI KCP Binjai Sudirman, and the implementation of Kur Mikro Syariah products at PT. BSI KCP Binjai Sudirman. This type of research is a qualitative type. The results showed that the Murabahah contract mechanism in financing products starts from completing the requirements in the murabahah bank BSI KCP Binjai Sudirman financing application application, which consists of the terms of the individual financing application and the terms of the application for legal entity / business entity financing. The stages of the financing process flow start from initiation, data collection, financing evaluation, financing decisions, and financing contracts. In analyzing the feasibility of financing KUR BSI KCP Binjai Sudirman, referring to the principles of 5C analysis which include; character, capacity, capital, condition of economy and collateral.